A pilot double-blind randomized placebo-controlled crossover pharmacodynamic study of the centrally active aminopeptidase A inhibitor, firibastat, in hypertension. Issue 8 (August 2019) - Azizi, Michel; Courand, Pierre-Yves; Denolle, Thierry; Delsart, Pascal; Zhygalina, Valentina; Amar, Laurence; Lantelme, Pierre; Mounier-Vehier, Claire; De Mota, Nadia; Balavoine, Fabrice; Llorens-Cortes, Catherine
Abstract : Objectives: We conducted a pilot multicenter double-blind randomized placebo-controlled crossover pharmacodynamic study to evaluate the blood pressure (BP) and the hormonal effects of firibastat, a first-in-class aminopeptidase A inhibitor prodrug, in patients with hypertension. Methods: Thirty-four patients with daytime ambulatory BP of at least 135/85 mmHg and less than 170/105 mmHg, after a 2-week run-in period were randomly assigned to receive either firibastat (250 mg b.i.d. for 1 week uptitrated to 500 mg b.i.d. for 3 weeks) and then placebo for 4 weeks each or vice versa, with a 2-week washout period on placebo. Results: At 4 weeks, daytime ambulatory systolic BP (SBP) decreased by 2.7 mmHg (95% confidence interval −6.5 to +1.1 mmHg) with firibastat versus placebo ( P  = 0.157). Office SBP decreased by 4.7 mmHg (95% confidence interval –11.1 to +1.8 mmHg) with firibastat versus placebo ( P  = 0.151). However, more the basal daytime ambulatory SBP was elevated, more the firibastat-induced BP decrease was marked. Firibastat did not influence 24h-ambulatory heart rate. Firibastat had no effect on plasma renin, aldosterone, apelin and copeptin concentrations. No major adverse events occurred. There was one episode of reversible skin allergy with facial edema. Conclusion: In patients with hypertension, a 4-week treatment with firibastat, tended to decrease daytime SBP relative to placebo. Firibastat did not modify the activity of the systemic renin–angiotensin system These results have justified designing a larger, powered trial of longer duration to fully assess its safety and effectiveness. Clinical trial registration: http://www.clinicaltrials.gov . NCT02322450. Abstract : Supplemental Digital Content is available in the text